The Role of Forsis LSM (Fort De Kock Society in Social) for Reach The Risk Groups of HIV / AIDS (Case Study: LGBT And Penasun Group s in The City of Padang) - Yanti, Anggun Mustika; Yuhelna, Yuhelna; Fitlayeni, Rinel (Jurnal ilmu sosial Mamangan (Padang), 2020)
One of the existing NGOs is FORSIS which is engaged in the grouping of HIV / AIDS risk groups to cope with the spread of HIV / AIDS in the city of Padang. The purpose of this study is to describe how the role of FORSIS in outreach groups at risk of HIV / AIDS in the city of Padang. The approach used in this research is a qualitative descriptive researcher, a technique used for data collection in interviews, observations, and document studies. In addition to the selection of informants is purposive sampling, which consists of informants who are considered to know about the role of FORSIS in outreach groups at risk of HIV / AIDS. The subjects in this research are Padang city community that is the board of FORSIS, LGBT group, caretaker of soul conscience, and LGBT with HIV. The results of this study are to describe the role of FORSIS in outreach groups at risk of HIV / AIDS. Prior to outreach there was a process planned for outreach. This NGO plays a role in improving community knowledge through socialization, then invites VCT to know the status of self so that can cope with the spread of viruses and NGOs also do cooperation with NGOs taratak soul heart to accompany PLWHA. It can be concluded that this FORSIS NGO plays an important role in providing counselling, inviting VCT and working with specific NGOs to assist in the prevention and transmission of HIV / AIDS.